This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( − 1 ) 2 n ± 1 = − 1 and ( − 1 ) 2 n = 1 where n is a positive non-zero integer
So can we write ( − 1 ) 9 9 9 9 9 9 9 4 3 7 8 as described in the way above
If 9 9 9 9 9 9 9 4 3 7 8 = 2 n ± 1 Then
9 9 9 9 9 9 9 4 3 7 8 ∓ 1 = 2 n
So
9 9 9 9 9 9 9 4 3 7 7 = 2 n ⇒ n = 4 9 9 9 9 9 9 7 1 8 8 . 5
and
9 9 9 9 9 9 9 4 3 7 9 = 2 n ⇒ n = 4 9 9 9 9 9 9 7 1 8 9 . 5
Neither of those answers fit the description of n so that means that
9 9 9 9 9 9 9 4 3 7 8 = 2 n
And since
( − 1 ) 2 n = 1
We can say that
( − 1 ) 9 9 9 9 9 9 9 4 3 7 8 = 1
( − 1 ) 2 n = 1 that,s it.
Problem Loading...
Note Loading...
Set Loading...
check the last digit if it is even answer is 1 or else -1